Exercise-associated muscle cramps and creatine kinase responses after workload spikes in a professional soccer player: a case study - Adriano Lima Alves; Igor Soalheiro; João Gustavo Claudino; Gerson Oliveira Rocha; Daniel Boullosa; André Gualberto Jafeth Alves; Eduardo Medonça Pimenta (Termedia Publishing House, 2022)
Purpose Exercise-associated muscle cramps (EAMC) are characterized by intense pain and involuntary contractions of a single muscle or muscle group. While EAMCs may occur during and after exercise, their precise aetiology remains unknown. However, there are some potential risk factors, as the workload of physical training previously performed. The purpose of this case report was to evaluate the acute:chronic workload ratio (ACWR) and creatine kinase (CK) concentrations in a professional soccer player to verify the potential influence of recent training history on an extreme EAMC episode and subsequent muscle damage. Methods A 21-year-old professional soccer player (body fat: 6.5%; body mass: 76 kg; height: 1.76 m) who experienced an extreme EAMC episode after the end of an official soccer match was monitored with session rating of perceived exertion before and after the EAMC episode and with post-match CK concentrations. Results ACWR revealed several spikes on the days before the match, with the highest one observed on the match day. The CK concentrations recorded 35 and 53 hours after the EAMC episode were 262% and 182% higher, respectively, than the maximal CK concentrations recorded during the season (703 U/l). Conclusions This case report illustrates, for the first time, how workload spikes, monitored with ACWR, preceded an extreme EAMC episode that was followed by an exacerbated muscle damage response. Some insights are provided in this case report for practitioners working in professional soccer to help them better manage similar cases.